Case report: Breaking CNS immuno-privilege: TNFα-inhibitor triggers aseptic meningitis in a patient with rheumatoid arthritis - Kassabian, Benedetta; Facco, Monica; Miscioscia, Alessandro; Carraro, Samuela; Rinaldi, Francesca; Gallo, Paolo; Puthenparampil, Marco (Frontiers in Immunology, 2024)
Disclosures: Benedetta Kassabian has nothing to disclose. A. Miscioscia received travel grant from Novartis, Sanofi-Genzyme, and Biogen. Samuela Carraro and Monica Facco have nothing to disclose. Puthenparampil Marco received travel grant from Novartis, Genzyme, Biogen, Teva, Almirall and Sanofi-Genzyme; he has been consultant for Sanofi-Genzyme, Novartis., Biogen. Rinaldi Francesca serves as an advisory board member of Biogen-Idec and has received funding for travel and speaker honoraria from Merck Serono, Biogen Idec, Sanofi-Aventis, Teva and Bayer Schering Pharma. Paolo Gallo reports grants and personal fees from Novartis, grants and personal fees from Almirall, grants and personal fees from Biogen Idec, grants and personal fees from Sanofi Genzyme, grants and personal fees from Teva, grants and personal fees from Merck Serono, grants from University of Padova, grants from Italian Ministry of Public Health, grants from Veneto Region of Italy, grants from Italian Association for Multiple Sclerosis, outside the submitted work.